1998
DOI: 10.1093/nar/26.16.3753
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA(guanine-26,N2-N2) methyltransferase (Trm1) from the hyperthermophilic archaeon Pyrococcus furiosus: cloning, sequencing of the gene and its expression in Escherichia coli

Abstract: The structural gene pfTRM1 (GenBank accession no. AF051912), encoding tRNA(guanine-26, N 2- N 2) methyltransferase (EC 2.1.1.32) of the strictly anaerobic hyperthermophilic archaeon Pyrococcus furiosus, has been identified by sequence similarity to the TRM1 gene of Saccharomyces cerevisiae (YDR120c). The pfTRM1 gene in a 3.0 kb restriction DNA fragment of P.furiosus genomic DNA has been cloned by library screening using a PCR probe to the 5'-part of the corresponding ORF. Sequence analysis revealed an entire O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The multisite-specific tRNA:m 5 C-methyltransferase (Trm4p/Ybl024p) obviously belongs to the recently discovered class of multisite-specific RNA modification enzymes (Simos et al+, 1996;Motorin et al+, 1998)+ The first member of this class, yeast RNA:pseudouridine synthase 1 (Pus1) is capable of catalyzing the formation of pseudouridine at eight distinct sites in tRNA and in one site in U2 snRNA in yeast Massenet et al+, 1999)+ The discovery of multisitespecific tRNA:m 5 C-methylase (Trm4) further reinforces the idea of the existence of other enzymes with rather "relaxed" substrate specificity and thus the capability of modifying numerous sites in cellular RNAs (tRNAs and probably in other RNA molecules)+ Further studies of the properties, functions, and substrate specificity of Trm4 should answer the question about the possible involvement of this enzyme in modification of other types of cellular RNAs+ (Perret et al+, 1990); tRNA Phe (GAA) (Sampson et al+, 1990); pre-tRNA Phe (GAA) (Reyes & Abelson, 1989); tRNA Ile (UAU) and tRNA Tyr (GUA) (Szweykowska-Kulinska et al+, 1994); and tRNA Ser (AGA) (Himeno et al+, 1997)+ They were kindly provided by R+ Giegé and F+ Fasiolo (Strasbourg, France), O+C+ Uhlenbeck (Boulder, Colorado, USA), Z+ Szweykowska-Kulinska (Poznan, Poland) and H+ Himeno (Tokyo, Japan)+ Preparation of the plasmid carrying the sequence corresponding to the anticodon stem-loop of yeast tRNA Phe (GAA) prolonged by a 19-nt-long natural intron (PheIVS minisubstrate) was described previously (Jiang et al+, 1997)+ Likewise, the minisubstrate bearing the anticodon stem-loop prolonged by the 32-nt natural intron of yeast tRNA Leu (CUA) downstream of the T7 promoter (LeuIVS minisubstrate) was prepared by PCR amplification of the corresponding sequence in the plasmid SUP53 CEN carrying the yeast SUP53 precursor tRNA gene (Strobel & Abelson, 1986; kindly provided by C+ Greer from Pasadena, California, USA)+ The PCR product was then cloned into the SmaI site of pUC118+ Plasmid pDC952 bearing the minor E. coli tRNA Arg (gene argU ) (Saxena & Walker, 1992) was kindly provided by Dr+ J+R+ Walker (Austin, Texas, USA)+ In vitro T7 RNA-polymerase transcription using [a 32 P]-radiolabeled nucleoside triphosphates and purification of the resulting T7 runoff tRNA transcripts by urea gels were performed as described elsewhere (Jiang et al+, 1997)+ Purification of total tRNA from E. coli and analysis of its nucleotide composition by postlabeling were performed as described previously (Constantinesco et al+, 1998)+ Hydrolysis of tRNA fractions and the HPLC analysis of nucleosides by reverse-phase chromatography on Lichrosphere 100RP18 (C 18 ) 5 mm column (250 ϫ 4+6 mm i+d+; Bischoff, Germany) were performed essentially as described in Gehrke & Kuo (1990)+…”
Section: Multisite-specific Enzymes In Eukaryotesmentioning
confidence: 99%
“…The multisite-specific tRNA:m 5 C-methyltransferase (Trm4p/Ybl024p) obviously belongs to the recently discovered class of multisite-specific RNA modification enzymes (Simos et al+, 1996;Motorin et al+, 1998)+ The first member of this class, yeast RNA:pseudouridine synthase 1 (Pus1) is capable of catalyzing the formation of pseudouridine at eight distinct sites in tRNA and in one site in U2 snRNA in yeast Massenet et al+, 1999)+ The discovery of multisitespecific tRNA:m 5 C-methylase (Trm4) further reinforces the idea of the existence of other enzymes with rather "relaxed" substrate specificity and thus the capability of modifying numerous sites in cellular RNAs (tRNAs and probably in other RNA molecules)+ Further studies of the properties, functions, and substrate specificity of Trm4 should answer the question about the possible involvement of this enzyme in modification of other types of cellular RNAs+ (Perret et al+, 1990); tRNA Phe (GAA) (Sampson et al+, 1990); pre-tRNA Phe (GAA) (Reyes & Abelson, 1989); tRNA Ile (UAU) and tRNA Tyr (GUA) (Szweykowska-Kulinska et al+, 1994); and tRNA Ser (AGA) (Himeno et al+, 1997)+ They were kindly provided by R+ Giegé and F+ Fasiolo (Strasbourg, France), O+C+ Uhlenbeck (Boulder, Colorado, USA), Z+ Szweykowska-Kulinska (Poznan, Poland) and H+ Himeno (Tokyo, Japan)+ Preparation of the plasmid carrying the sequence corresponding to the anticodon stem-loop of yeast tRNA Phe (GAA) prolonged by a 19-nt-long natural intron (PheIVS minisubstrate) was described previously (Jiang et al+, 1997)+ Likewise, the minisubstrate bearing the anticodon stem-loop prolonged by the 32-nt natural intron of yeast tRNA Leu (CUA) downstream of the T7 promoter (LeuIVS minisubstrate) was prepared by PCR amplification of the corresponding sequence in the plasmid SUP53 CEN carrying the yeast SUP53 precursor tRNA gene (Strobel & Abelson, 1986; kindly provided by C+ Greer from Pasadena, California, USA)+ The PCR product was then cloned into the SmaI site of pUC118+ Plasmid pDC952 bearing the minor E. coli tRNA Arg (gene argU ) (Saxena & Walker, 1992) was kindly provided by Dr+ J+R+ Walker (Austin, Texas, USA)+ In vitro T7 RNA-polymerase transcription using [a 32 P]-radiolabeled nucleoside triphosphates and purification of the resulting T7 runoff tRNA transcripts by urea gels were performed as described elsewhere (Jiang et al+, 1997)+ Purification of total tRNA from E. coli and analysis of its nucleotide composition by postlabeling were performed as described previously (Constantinesco et al+, 1998)+ Hydrolysis of tRNA fractions and the HPLC analysis of nucleosides by reverse-phase chromatography on Lichrosphere 100RP18 (C 18 ) 5 mm column (250 ϫ 4+6 mm i+d+; Bischoff, Germany) were performed essentially as described in Gehrke & Kuo (1990)+…”
Section: Multisite-specific Enzymes In Eukaryotesmentioning
confidence: 99%
“…It is noteworthy that this purified Trm1 fraction does not contain any nucleic acids. In the case of purification of P. furiosus Trm1, it has been reported that RNA bound tightly to the recombinant protein, and that RNase A treatment is effective for removal of the RNA (18). We also observed contamination by RNA in the A. aeolicus Trm1 fraction during the purification steps; however, we could separate (Fig.…”
Section: Putative Trm1 Gene Is Encoded In the A Aeolicus Genome Andmentioning
confidence: 53%
“…The most highly purified enzyme from a native source was obtained from Tetrahymena pyriformis (4). The responsible gene was first determined to be trm1 from Saccharomyces cerevisiae (13,14) and then experimentally identified from various eukaryotes (Schizosaccharomyces pombe (15), Caenorhabditis elegans (16), and human (17)) and archaea (Pyrococcus furiosus (18), Pyrococcus horikoshii (19), and Haloferax volcanii (20)), as is consistent with the distribution of the m G modifications in tRNA can be found not only at position 26 but also at positions 6, 7, 9, 10, 18, and 27 in various organisms (21). However, only m 2 2 G10 formation enzymes (the Trm11-Trm112 complex in yeast (22) and Trmm 2 2 G10 enzyme in Pyrococcus abyssi (23,24)) have been identified thus far.…”
mentioning
confidence: 99%
“…The most highly purified enzyme from a native source was obtained from Tetrahymena pyriformis (4). The responsible gene was first determined to be trm1 from Saccharomyces cerevisiae (13,14) and then experimentally identified from various eukaryotes (Schizosaccharomyces pombe (15), Caenorhabditis elegans (16), and human (17)) and archaea (Pyrococcus furiosus (18), Pyrococcus horikoshii (19), and Haloferax volcanii (20)), consistent with the distribution of the m 2 2 G26 (or m 2 G26) modification in tRNA. Furthermore, we have recently reported that Aquifex aeolicus, a hyper-thermophilic eubacterium, has a Trm1 protein that catalyzes methyl transfer not only to G26 but also to G27 (21).…”
mentioning
confidence: 88%